2021
DOI: 10.3389/fnagi.2021.729949
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Sorghum Polyphenols to Prevent and Treat Alzheimer’s Disease: A Review Article

Abstract: Alzheimer’s disease (AD) is characterized by the excessive deposition of extracellular amyloid-beta peptide (Aβ) and the build-up of intracellular neurofibrillary tangles containing hyperphosphorylated tau proteins. This leads to neuronal damage, cell death and consequently results in memory and learning impairments leading to dementia. Although the exact cause of AD is not yet clear, numerous studies indicate that oxidative stress, inflammation, and mitochondrial dysfunction significantly contribute to its on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 307 publications
(372 reference statements)
0
13
0
Order By: Relevance
“…There are a number of studies using a combination of polyphenol extracts, collected from natural sources, suggesting a therapeutic potential to alleviate or arrest sleep deprivation or stress-dependent cognitive deterioration [ 62 , 63 ]. In addition, the beneficial effect of polyphenolic components against AD-type cognitive decline, Aβ peptide accumulation in the brain, and tauopathies has been reported [ 64 , 65 , 66 , 67 ]. Accordingly, our data showed that MG improved CUS-induced anxiety and depression-related behavior, as indicated by more exposure to open spaces in the EPM and an increase in motility in the forced swim test, therefore promoting resilience in those animals subjected to chronic stress.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of studies using a combination of polyphenol extracts, collected from natural sources, suggesting a therapeutic potential to alleviate or arrest sleep deprivation or stress-dependent cognitive deterioration [ 62 , 63 ]. In addition, the beneficial effect of polyphenolic components against AD-type cognitive decline, Aβ peptide accumulation in the brain, and tauopathies has been reported [ 64 , 65 , 66 , 67 ]. Accordingly, our data showed that MG improved CUS-induced anxiety and depression-related behavior, as indicated by more exposure to open spaces in the EPM and an increase in motility in the forced swim test, therefore promoting resilience in those animals subjected to chronic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols are naturally occurring compounds and secondary metabolites of plants, generally produced to protect plants against biotic and abiotic stressors, acting as antioxidant, anti-inflammatory, antimicrobial, anti-diabetic, and anticancer molecules [43,44]. Total phenolic and flavonoids content of BAO were measured; the results are summarized in (Table 2).…”
Section: Total Phenolic and Flavonoids Contentsmentioning
confidence: 99%
“…Phenolic acids are wildly distributed in natural sources (fruits, coffee, tea, and grains), have long stability in foods and show a high intestinal intake [ 216 ] and efficient brain absorption [ 217 ]. These compounds have shown good effects in models of AD [ 218 ]; however, the effect in primary tauopathies has not been studied. Due to their diverse neuroprotective effects, which have been extensively reviewed elsewhere [ 218 , 219 ], phenolic acids are considered potential candidates to treat tauopathies.…”
Section: Antioxidant Therapies For the Treatment Of Tauopathiesmentioning
confidence: 99%
“…These compounds have shown good effects in models of AD [ 218 ]; however, the effect in primary tauopathies has not been studied. Due to their diverse neuroprotective effects, which have been extensively reviewed elsewhere [ 218 , 219 ], phenolic acids are considered potential candidates to treat tauopathies.…”
Section: Antioxidant Therapies For the Treatment Of Tauopathiesmentioning
confidence: 99%